Electrode for solid-state battery and solid-state battery

By integrating specific metals within the electrode layers of solid-state batteries, the resistance increase is mitigated, enhancing the performance and durability of these batteries through improved electronic conductivity and ionic stability.

JP2025007393AActive Publication Date: 2025-01-17TOYOTA JIDOSHA KK +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023108759
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

Solid-state batteries experience an increase in resistance due to repeated charging and discharging, which accelerates battery deterioration.

Method used

Incorporating specific metals such as copper, silver, nickel, iron, and others into the positive or negative electrode layers of solid-state batteries, with a volume content between 5 ppm and 10,000 ppm, to react with the sulfide solid electrolyte and enhance electronic conductivity, thereby reducing resistance.

Benefits of technology

The proposed solution effectively suppresses the increase in resistance and maintains ionic conductivity, improving the performance and longevity of solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007393000007
    Figure 2025007393000007
  • Figure 2025007393000001
    Figure 2025007393000001
  • Figure 2025007393000002
    Figure 2025007393000002
Patent Text Reader

Abstract

To provide an electrode for a solid-state battery and a solid-state battery that can reduce the increase in resistance of the solid-state battery.SOLUTION: An electrode for a solid state battery includes a sulfide solid electrolyte, and a metal that reacts with the sulfide solid electrolyte to exhibit electronic conductivity, and the content of the metal relative to the total volume of the electrode for a solid state battery is 5 ppm by volume or more and less than 10,000 ppm by volume.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an electrode for a solid-state battery and a solid-state battery. [Background technology]

[0002] In recent years, with the rapid spread of information-related devices and communication devices such as personal computers, video cameras, and mobile phones, the development of batteries to be used as power sources for these devices has become important. Among these, lithium-ion batteries have attracted attention due to their high energy density and excellent safety.

[0003] Conventionally, batteries used for such applications have used electrolytes containing flammable organic solvents, which necessitates the installation of safety devices to suppress temperature rise during short circuits, and improvements in structure and materials to prevent short circuits.In response to this, development is being carried out on batteries in which the electrolyte is replaced with a solid electrolyte layer, as this makes it possible to avoid the use of flammable organic solvents in the battery, simplify the safety devices, and improve manufacturing costs and productivity.

[0004] Generally, when the positive electrode layer and the negative electrode layer of a solid-state battery contain a metal such as copper, this metal is removed because there is a risk of causing a short circuit. For example, in Patent Document 1, a solid-state battery including a positive electrode layer, a sulfide solid electrolyte layer, and a negative electrode layer is aged before the first charge, whereby metals such as copper are dissolved and removed. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2020-191183 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, the resistance of a solid-state battery tends to increase as the battery is repeatedly charged and discharged. An increase in the rate of increase in resistance means that the deterioration of the battery caused by charging and discharging the battery increases. The present inventors have now found that the above-mentioned increase in resistance can be suppressed by incorporating a specific metal in a specific content in the positive electrode layer or the negative electrode layer.

[0007] One embodiment of the present disclosure has been made in consideration of the above circumstances, and an object of the present disclosure is to provide an electrode for a solid-state battery and a solid-state battery capable of reducing an increase in resistance of the solid-state battery. [Means for solving the problem]

[0008] Means for solving the above problems include the following embodiments. <1> A sulfide solid electrolyte; A metal that reacts with the sulfide solid electrolyte to exhibit electronic conductivity; Contains A solid-state battery electrode, in which the content of the metal relative to the total volume of the electrode for the solid-state battery is 5 ppm by volume or more and less than 10,000 ppm by volume. <2> The metal is at least one metal selected from the group consisting of copper, silver, nickel, iron, tin, aluminum, titanium, chromium, zinc, gold, magnesium, antimony, zirconium, molybdenum, and alloys thereof. <1> The electrode for a solid-state battery according to claim 1. <3> The metal is at least one of copper and silver. <2> The electrode for a solid-state battery according to claim 1. <4> The content of the metal relative to the total volume of the electrode for a solid-state battery is 50 ppm by volume or more. <1> ~ <3> 13. An electrode for a solid battery according to claim 12. <5> The content of the metal relative to the total volume of the electrode for a solid state battery is 5,000 ppm by volume or less. <1> ~ <4> 13. An electrode for a solid battery according to claim 12. <6> The sulfide solid electrolyte contains phosphorus atoms. <1> ~ <5> 13. An electrode for a solid battery according to claim 12. <7> A solid-state battery comprising a positive electrode layer, a solid electrolyte layer, and a negative electrode layer, At least one of the positive electrode layer and the negative electrode layer is <1> ~ <6> 13. A solid-state battery comprising the electrode for a solid-state battery according to any one of claims 1 to 12. Effect of the Invention

[0009] According to an embodiment of the present disclosure, it is possible to provide an electrode for a solid-state battery and a solid-state battery capable of reducing an increase in resistance of the solid-state battery. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of the solid electrolyte of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] In the present disclosure, a numerical range indicated using "~" means a range that includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in the present disclosure. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples. In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In the present disclosure, when there are multiple substances corresponding to each component, the amount of each component means the total amount of the multiple substances, unless otherwise specified. In this disclosure, "solid electrolyte" refers to an electrolyte that remains solid at 25° C. under a nitrogen atmosphere. In the present disclosure, the "sulfide solid electrolyte" includes both a crystalline sulfide solid electrolyte having a crystal structure and an amorphous sulfide solid electrolyte. In the present disclosure, the crystalline sulfide solid electrolyte is a solid electrolyte in which a peak derived from the solid electrolyte is observed in the X-ray diffraction pattern in a powder X-ray diffraction (XRD) measurement, and it does not matter whether or not there is a peak derived from the raw material of the solid electrolyte. That is, the crystalline sulfide solid electrolyte includes a crystal structure derived from the solid electrolyte, and a part of the crystal structure may be derived from the solid electrolyte, or the whole of the crystal structure may be derived from the solid electrolyte. And, as long as the crystalline sulfide solid electrolyte has the above-mentioned X-ray diffraction pattern, it may include an amorphous sulfide solid electrolyte (also called a "glass component") in a part of it. Therefore, the crystalline sulfide solid electrolyte includes so-called glass ceramics obtained by heating the amorphous solid electrolyte (glass component) to a crystallization temperature or higher. In the present disclosure, the amorphous sulfide solid electrolyte (glass component) refers to one in which the X-ray diffraction pattern in a powder X-ray diffraction (XRD) measurement is a halo pattern in which no peaks other than those derived from the material are observed, and it does not matter whether or not there are peaks derived from the raw materials of the solid electrolyte.

[0012] [Solid battery electrode] The electrode for a solid state battery according to the present disclosure contains a sulfide solid electrolyte and a metal that reacts with the sulfide solid electrolyte to exhibit electronic conductivity (hereinafter also referred to as a "specific metal"); The content of the metal relative to the total volume of the electrode for a solid-state battery is 5 ppm by volume or more and less than 10,000 ppm by volume.

[0013] According to the electrode for a solid-state battery according to the present disclosure, an increase in the resistance of a solid-state battery can be reduced. The reason why the above effect is achieved is not clear, but is presumed to be as follows. When the electrode for a solid battery according to the present disclosure contains a sulfide solid electrolyte and a specific metal of 5 volume ppm or more, the sulfide solid electrolyte and the specific metal react during heat generation at the time of charge and discharge, and a metal sulfide or a metal thiophosphate is generated. Since these are excellent in electron conductivity, it is presumed that the efficiency of the electron conduction path is improved and an increase in resistance is suppressed. Further, it is presumed that the sulfide solid electrolyte is imparted with electron conductivity by the reaction of the sulfide solid electrolyte and the specific metal, and an increase in resistance is suppressed. Furthermore, by setting the content of the specific metal in the electrode for a solid battery according to the present disclosure to less than 10,000 volume ppm, it is possible to suppress a decrease in ionic conductivity, and it is presumed that an increase in resistance is suppressed.

[0014] (sulfide solid electrolyte) The sulfide solid electrolyte can contain lithium atoms, sulfur atoms, and halogen atoms. From the viewpoint of reacting the sulfide solid electrolyte and the specific metal to further suppress an increase in resistance, the sulfide solid electrolyte preferably contains a phosphorus atom. When the sulfide solid electrolyte contains a phosphorus atom, a metal thiophosphate is generated, and both ionic conductivity and electron conductivity can be achieved. The sulfide solid electrolyte may be amorphous or crystalline.

[0015] In one embodiment, the composition of the sulfide solid electrolyte is represented by, for example, xLi2S·(100−x)P2S5 (70≤x≤80), yLiI·zLiBr·(100−y−z)(xLi2S·(1−x)P2S5) (0.7≤x≤0.8, 0≤y≤30, 0≤z≤30), etc. Further, the sulfide solid electrolyte may have a composition represented by the following general formula (1). Li 4-x Ge 1-x P x S4 (0 < x < 1) ··· Formula (1) In formula (1), at least a portion of Ge may be substituted with at least one selected from the group consisting of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V, and Nb. At least a portion of P may be substituted with at least one selected from the group consisting of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V, and Nb. At least a portion of Li may be substituted with at least one selected from the group consisting of Na, K, Mg, Ca, and Zn. At least a portion of S may be substituted with a halogen. The halogen is at least one of F, Cl, Br, and I.

[0016] Examples of amorphous sulfide solid electrolytes include solid electrolytes composed of lithium sulfide, phosphorus sulfide, and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, and Li2S-P2S5-LiI-LiBr; and solid electrolytes further containing other atoms such as oxygen atoms and silicon atoms, such as Li2S-P2S5-Li2O-LiI and Li2S-SiS2-P2S5-LiI. From the viewpoint of obtaining higher ionic conductivity, preferred examples of the solid electrolyte include those composed of lithium sulfide, phosphorus sulfide, and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, and Li2S-P2S5-LiI-LiBr. The types of atoms constituting the amorphous sulfide solid electrolyte can be confirmed, for example, by an ICP emission spectroscopic analyzer. The crystalline sulfide solid electrolyte may be a so-called glass ceramic obtained by heating an amorphous solid electrolyte to a crystallization temperature or higher. The crystal structure of the glass ceramic may be Li3PS4 crystal structure, Li4P2S6 crystal structure, Li7PS6 crystal structure, Li7P3S 11 crystalline structure, and crystalline structure having peaks at 2θ=approximately 20.2° and 23.6° (for example, JP 2013-16423 A). 4-x Ge 1-x P xS4 thio-LISICON Region II crystal structure (Kanno et al., Journal of The Electrochemical Society, 148(7)A742-746(2001)), Li 4-x Ge 1-x P x Examples include a crystal structure similar to the S4 thio-LISICON Region II type (see Solid State Ionics, 177 (2006), 2721-2725).

[0017] The shape of the sulfide solid electrolyte is not particularly limited, but may be, for example, particulate. The average particle diameter (D 50 ) can be, for example, in the range of 0.01 μm to 500 μm, or 0.1 to 200 μm.

[0018] The content of the sulfide solid electrolyte relative to the total mass of the solid battery electrode is preferably 2 mass % to 90 mass %, and more preferably 5 mass % to 30 mass %. The content (volume ratio) of the sulfide solid electrolyte relative to the total volume of the solid state battery electrode is preferably 3 volume % to 95 volume %, and more preferably 4 volume % to 85 volume %.

[0019] (Specific metal) The solid-state battery electrode according to the present disclosure contains a metal (specific metal) that reacts with a sulfide solid electrolyte to exhibit electronic conductivity. Examples of the specific metal include at least one metal selected from copper, silver, nickel, iron, tin, aluminum, titanium, chromium, zinc, gold, magnesium, antimony, zirconium, molybdenum, and alloys thereof. Among the above, at least one of copper and silver is preferred, and copper is more preferred, from the viewpoint of further reducing the increase in resistance. The shape of the metal is not particularly limited, and may be particulate or non-particulate.

[0020] Here, a method for verifying whether a metal is a metal (specific metal) that reacts with a sulfide solid electrolyte to exhibit electronic conductivity will be described. First, the metal to be verified is mixed with a sulfide solid electrolyte, and a sample is obtained by heat treatment. At this time, the mixing conditions and heat treatment conditions are set as follows. Mixing conditions: Mix the sulfide solid electrolyte and the target metal (using metal powder) so that the volume concentration of the metal powder is 5%. Weigh out 1 g of the sulfide solid electrolyte and the metal powder so that the volume concentration is 5%, and thoroughly dry mix them in a mortar for 5 minutes to obtain a mixed powder. Heat treatment conditions: The Swagelok cell shown below is placed in a thermostatic chamber set at 150°C and heat treated for 7 days. After 7 days, it is removed from the thermostatic chamber and cooled to 25°C, after which the electronic conductivity after heat treatment is measured.

[0021] Next, the electronic conductivity of the obtained sample is measured before and after the heat treatment by the following method. Weigh out 200 mg of the sample and place it in a Swagelok cylinder at 1 ton / cm 2 The pellet is pressed with a pressure of 0.01 V. Both ends of the pellet are clamped with SUS pins and bolted to apply a confining pressure to the pellet. The pellet is sealed in a Swagelok cylinder, which is called a Swagelok cell. For samples after heat treatment, the Swagelok cell is subjected to heat treatment under the above heat treatment conditions. The electronic conductivity of the sample is calculated by DC polarization while keeping it at 25°C. For the measurement, Celltest and Solartron 1260, both manufactured by Solartron, are used. Voltages of 0.1V, 0.2V, and 0.3V are applied for 30 seconds, and the amount of current passing is measured. Resistance is calculated from the relationship between the applied voltage and the amount of current passing, and electronic conductivity is calculated.

[0022] The electronic conductivity before and after the heat treatment is then compared. The increase rate of electronic conductivity is calculated by dividing the electronic conductivity after the heat treatment by the electronic conductivity before the heat treatment. If the increase rate of electronic conductivity is 2.17 or more, it is determined to be a metal (specific metal) that reacts with the sulfide solid electrolyte and exhibits electronic conductivity.

[0023] When the specific metal is in the form of particles, the smaller the particle size, the greater the reactivity with the sulfide solid electrolyte and the greater the effect.

[0024] From the viewpoint of reacting the sulfide solid electrolyte and the specific metal to further reduce the increase in resistance, the content of the specific metal relative to the total volume of the electrode for solid state batteries is preferably 20 ppm by volume or more, more preferably 100 ppm by volume or more, even more preferably 200 ppm by volume or more, particularly preferably 450 ppm by volume or more, most preferably 600 ppm by volume or more, and may be 1000 ppm by volume or more. From the viewpoint of suppressing a decrease in ionic conductivity and further reducing an increase in resistance, the content of the specific metal relative to the total volume of the electrode for a solid battery is preferably 8000 volume ppm or less, more preferably 7000 volume ppm or less, even more preferably 6000 volume ppm or less, particularly preferably 5500 volume ppm or less, and may be 5000 volume ppm or less. Furthermore, from the viewpoint of reducing the self-discharge amount and suppressing short circuits, the content of the specific metal relative to the total volume of the electrode for a solid battery is more preferably 4000 volume ppm or less, and even more preferably 3000 volume ppm or less.

[0025] In the present disclosure, the content (volume ratio) of a specific metal in an electrode for a solid state battery can be measured by the following method. The cross section of an electrode for a solid-state battery is observed using a scanning electron microscope equipped with EDS (SEM-EDS, magnification 30,000x), and the content (volume ratio) of a specific metal can be measured by performing elemental analysis using energy dispersive spectroscopy (EDS).

[0026] (active material) The solid-state battery electrode according to the present disclosure may include an active material. The active material may be a positive electrode active material or a negative electrode active material.

[0027] The positive electrode active material preferably contains a lithium composite oxide. The lithium composite oxide may contain at least one selected from the group consisting of F, Cl, N, S, Br, and I. The lithium composite oxide may have a crystal structure belonging to at least one space group selected from the space groups R-3m, Immm, and P63-mmc (also called P63mc or P6 / mmc). The lithium composite oxide may have an O2 type structure in which the transition metal, oxygen, and lithium are mainly arranged. Examples of lithium composite oxides having a crystal structure belonging to R-3m include Li x Me y O α X β (Me represents at least one selected from the group consisting of Mn, Co, Ni, Fe, Al, Cu, V, Nb, Mo, Ti, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, Ag, Ru, W, B, Si, and P, and X represents at least one selected from the group consisting of F, Cl, N, S, Br, and I, and satisfies 0.5≦x≦1.5, 0.5≦y≦1.0, 1≦α<2, and 0<β≦1.) Examples of lithium composite oxides having a crystal structure belonging to Immm include Li x1 M 1 A 1 2(1.5≦x1≦2.3, M 1 contains at least one selected from the group consisting of Ni, Co, Mn, Cu and Fe, and A 1 contains at least oxygen, and A 1 The ratio of oxygen in the oxide is 85 atomic % or more. x1 M 1A 1-x2 M 1B x2 O 2-y A 2 y (0≦x2≦0.5, 0≦y≦0.3, and at least one of x2 and y is not 0; M 1A represents at least one selected from the group consisting of Ni, Co, Mn, Cu, and Fe, and M 1Brepresents at least one selected from the group consisting of Al, Mg, Sc, Ti, Cr, V, Zn, Ga, Zr, Mo, Nb, Ta, and W, and A2 represents at least one selected from the group consisting of F, Cl, Br, S, and P. A complex oxide represented by ) can be mentioned. Examples of the lithium complex oxide having a crystal structure belonging to P63-mmc include, for example, M1 x M2 y O2 (where M1 represents an alkali metal (at least one of Na and K is preferable), M2 represents a transition metal (at least one selected from the group consisting of Mn, Ni, Co, and Fe is preferable), and x + y satisfies 0 < x + y ≦ 2). A complex oxide represented by ) can be mentioned. Examples of the lithium complex oxide having an O2-type structure include, for example, Li x [Li α (Mn a Co b M c ) 1-α O2 (0.5 < x < 1.1, 0.1 < α < 0.33, 0.17 < a < 0.93, 0.03 < b < 0.50, 0.04 < c < 0.33, and M represents at least one selected from the group consisting of Ni, Mg, Ti, Fe, Sn, Zr, Nb, Mo, W, and Bi). A complex oxide represented by ) can be mentioned, and specific examples include Li 0.744 [Li 0.145 Mn 0.625 Co 0.115 Ni 0.115 O2 and the like.

[0028] Examples of the negative electrode active material include silicon, silicon alloy, silicon oxide, etc. Further, as the negative electrode active material, metal lithium, metal indium, metal aluminum, metal silicon, metal tin, etc., metals that can form an alloy with metal lithium, oxides of these metals, alloys of these metals and metal lithium, etc. may be used. Examples of the oxide include, for example, Li4Ti5O 12Examples of oxide active materials include the above. Furthermore, examples of negative electrode active materials include carbon. Examples of carbon include natural graphite, artificial graphite, hard carbon (hardly graphitizable carbon), and soft carbon (easily graphitizable carbon). Examples of artificial graphite include highly oriented graphite and mesocarbon microbeads.

[0029] The content of the active material in each of the positive electrode and negative electrode in the solid battery electrode according to the present disclosure is preferably 20% by mass to 99% by mass, and more preferably 50% by mass to 90% by mass, based on the total mass of the positive electrode or the total mass of the negative electrode. However, for the negative electrode, when Li metal or the like is used, the content of the active material may be 100% by mass. The content (volume ratio) of the active material in each of the positive electrode and negative electrode is preferably 10 volume % to 99 volume %, and more preferably 32 volume % to 81 volume %, relative to the total volume of the positive electrode or the total volume of the negative electrode.

[0030] (Conductive assistant) The solid state battery electrode according to the present disclosure can include a conductive assistant. Examples of the conductive assistant include carbon-based materials such as artificial graphite, graphite carbon fiber, resin-calcined carbon, pyrolytic vapor-grown carbon, coke, mesocarbon microbeads, furfuryl alcohol resin-calcined carbon, polyacene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, and non-graphitizable carbon.

[0031] The content of the conductive assistant in each of the positive electrode and the negative electrode in the electrode for a solid battery according to the present disclosure is preferably 0% by mass to 20% by mass, and more preferably 0% by mass to 3% by mass, relative to the total mass of the positive electrode or the total mass of the negative electrode. The content (volume ratio) of the conductive assistant in each of the positive electrode and the negative electrode is preferably 0 volume % to 45 volume %, and more preferably 0 volume % to 5.5 volume %, relative to the total volume of the positive electrode or the total volume of the negative electrode.

[0032] (binder) The solid state battery electrode according to the present disclosure can include a binder. Examples of binders include fluorine-based polymers such as polytetrafluoroethylene and polyvinylidene fluoride, thermoplastic elastomers such as butylene rubber and styrene-butadiene rubber, and various resins such as acrylic resin, acrylic polyol resin, polyvinyl acetal resin, polyvinyl butyral resin, and silicone resin.

[0033] The binder content in each of the positive electrode and negative electrode in the solid battery electrode according to the present disclosure is preferably 0% by mass to 10% by mass, and more preferably 0% by mass to 3% by mass, relative to the total mass of the positive electrode or the total mass of the negative electrode. The content (volume ratio) of the binder in each of the positive electrode and the negative electrode is preferably 0 volume % to 42.5 volume % and more preferably 0 volume % to 12 volume % relative to the total volume of the positive electrode or the total volume of the negative electrode.

[0034] (Other Ingredients) The electrode for a solid battery according to the present disclosure may contain components other than the above-mentioned components (hereinafter, also referred to as "other components"). Examples of the other components include solid electrolytes other than sulfide solid electrolytes. Examples of solid electrolytes other than sulfide solid electrolytes include oxide solid electrolytes and halogenated solid electrolytes. The oxide solid electrolyte preferably contains oxygen (O) as a main component of an anion element, and may contain, for example, Li, Q element (Q represents at least one of Nb, B, Al, Si, P, Ti, Zr, Mo, W, and S), and O. Examples of the oxide solid electrolyte include garnet-type solid electrolytes, perovskite-type solid electrolytes, Nasicon-type solid electrolytes, Li-PO-based solid electrolytes, and Li-BO-based solid electrolytes. Examples of the garnet-type solid electrolyte include Li7La3Zr2O 12 , Li 7-x La3(Zr 2-x Nb x )O 12 (0≦x≦2), Li5La3Nb2O 12Examples include etc. Examples of perovskite-type solid electrolytes include, for example, (Li, La)TiO3, (Li, La)NbO3, (Li, Sr)(Ta, Zr)O3, etc. Examples of NASICON-type solid electrolytes include, for example, Li(Al, Ti)(PO4)3, Li(Al, Ga)(PO4)3, etc. Examples of Li-P-O-based solid electrolytes include Li3PO4, LIPON (a compound in which a part of O in Li3PO4 is replaced by N), and examples of Li-B-O-based solid electrolytes include Li3BO3, a compound in which a part of O in Li3BO3 is replaced by C, etc. As the halide solid electrolyte, a solid electrolyte containing Li, M, and X (M represents at least one of Ti, Al, and Y, and X represents F, Cl, or Br) is suitable. Specifically, Li 6-3z Y z X6 (X represents Cl or Br, and z satisfies 0 < z < 2), Li 6-(4-x)b (Ti 1-x Al x ) b F6 (0 < x < 1, 0 < b ≦ 1.5) is preferred. Among Li 6-3z Y z X6, Li3YX6 (X represents Cl or Br) is more preferred in terms of excellent lithium ion conductivity, and further Li3YCl6 is preferred. Also, Li 6-(4-x)b (Ti 1-x Al x ) b F6 (0 < x < 1, 0 < b ≦ 1.5) is preferably contained together with a solid electrolyte such as a sulfide solid electrolyte, for example, from the viewpoint of suppressing oxidative decomposition of the sulfide solid electrolyte, etc., and more preferably covers at least a part of the surface of the solid electrolyte such as the sulfide solid electrolyte. Thereby, the lithium ion conductivity becomes better.

[0035] (Use) The electrode for a solid battery according to the present disclosure can be suitably used as a material constituting the positive electrode or the negative electrode of a solid battery.

[0036] [Solid battery] The solid battery according to the present disclosure includes a positive electrode layer, a solid electrolyte layer, and a negative electrode layer. At least one of the positive electrode layer and the negative electrode layer is an electrode for a solid battery according to the present disclosure.

[0037] The solid-state battery according to the present disclosure may include a positive electrode current collector on the side of the positive electrode layer opposite to the solid electrolyte layer side. The solid-state battery according to the present disclosure may include a negative electrode current collector on the side of the negative electrode layer opposite to the solid electrolyte layer side.

[0038] (Positive and negative electrode layers) At least one of the positive electrode layer and the negative electrode layer included in the solid-state battery according to the present disclosure is the solid-state battery electrode according to the present disclosure. The configuration of the solid-state battery electrode other than the solid-state battery electrode according to the present disclosure is not particularly limited and may be a conventionally known configuration, for example, an electrode having a configuration that does not contain a specific metal in the solid-state battery electrode according to the present disclosure. The electrode for a solid-state battery according to the present disclosure has been described above, and therefore a description thereof will be omitted here. The thickness of the positive electrode layer is not particularly limited, and can be, for example, 1 nm or more and 500 μm or less. The thickness of the negative electrode layer is not particularly limited, and can be, for example, 1 nm or more and 500 μm or less.

[0039] (Solid electrolyte layer) The solid electrolyte layer may contain a solid electrolyte. The solid electrolyte layer may have a single-layer structure or a multi-layer structure of two or more layers. As the solid electrolyte, a conventionally known one that can be used for the solid electrolyte layer of a solid battery can be used, and for example, a sulfide solid electrolyte can be used.

[0040] The solid electrolyte layer may contain a binder, such as a rubber-based binder such as styrene-butadiene rubber, or a fluoride-based binder such as polyvinylidene fluoride (PVDF).

[0041] The thickness of the solid electrolyte layer is not particularly limited, and can be, for example, 1 nm or more and 500 μm or less.

[0042] (Positive electrode current collector) The positive electrode current collector may be a conventionally known one. The positive electrode current collector may be stainless steel, aluminum, nickel, iron, titanium, carbon, etc., and is preferably an aluminum alloy foil or aluminum foil. The aluminum alloy foil and aluminum foil may be manufactured using powder. The shape of the positive electrode current collector may be, for example, a foil or mesh shape.

[0043] The thickness of the positive electrode current collector is not particularly limited, and can be, for example, 1 nm or more and 50 μm or less.

[0044] (Negative electrode current collector) The negative electrode current collector can be made of the above-mentioned metal foil, and nickel foil and aluminum foil are preferred. The thickness of the negative electrode current collector is not particularly limited, and can be, for example, 1 nm or more and 50 μm or less.

[0045] A schematic cross-sectional view showing one embodiment of a solid-state battery according to the present disclosure is shown in Fig. 1. As shown in Fig. 1, an anode layer A, a solid electrolyte layer B, and a cathode layer C are laminated. In FIG. 1, the negative electrode active material is indicated by reference numeral 101 , the positive electrode active material is indicated by reference numeral 103 , the conductive assistants are indicated by reference numerals 105 and 107 , the binders are indicated by reference numerals 109 and 111 , the negative electrode current collector is indicated by reference numeral 113 , and the positive electrode current collector is indicated by reference numeral 115 . At least one of the negative electrode layer A and the positive electrode layer C contains a specific metal (not shown). The solid-state battery may have a structure in which the laminated end faces (side faces) of the laminated structure of the positive electrode / solid electrolyte layer / negative electrode are sealed with a resin. The positive electrode current collector and the negative electrode current collector may have a buffer layer, an elastic layer, or a PTC (Positive Temperature Coefficient) thermistor layer disposed on the surface. The solid electrolyte layer may have a two-layer structure as shown in FIG.

[0046] An embodiment of the method for producing a solid-state battery according to the present disclosure will be described below, but the present disclosure is not limited thereto. First, a positive electrode mixture paste, in which a sulfide solid electrolyte, a specific metal, a positive electrode active material, a conductive assistant, a binder, and the like are dissolved or dispersed in an arbitrary solvent, is applied onto a positive electrode current collector, and then dried to form a positive electrode layer, thereby producing a positive electrode sheet including a positive electrode current collector and a positive electrode layer. Next, a negative electrode mixture paste in which a sulfide solid electrolyte, a specific metal, a negative electrode active material, a conductive assistant, a binder, etc. are dissolved or dispersed in an arbitrary solvent is applied to the upper surface of the negative electrode current collector, and then dried to form a negative electrode layer, thereby producing a negative electrode sheet including a negative electrode current collector and a negative electrode layer. Next, a paste for a solid electrolyte layer, in which a solid electrolyte, a binder, and the like are dissolved or dispersed in an arbitrary solvent, is applied onto a metal foil such as an aluminum foil (e.g., a SUS foil), and dried to form a solid electrolyte layer, thereby producing a solid electrolyte sheet including the metal foil and the solid electrolyte layer. Next, the negative electrode sheet and the solid electrolyte sheet are laminated and pressed to transfer the solid electrolyte layer onto the surface of the negative electrode layer. Next, a positive electrode sheet is laminated on the side of the solid electrolyte layer opposite the negative electrode layer side, and pressed to produce a solid-state battery. The solid-state battery produced by the above method includes a positive electrode current collector, a positive electrode layer, a solid electrolyte layer, a negative electrode layer, and a negative electrode current collector in this order. Examples of the solvent include water, N-methyl-2-pyrrolidone, butyl butyrate, tetrahydronaphthalene, heptane, dibutyl ether, and diisobutyl ketone (DIBK). EXAMPLES

[0047] The present disclosure will be described in more detail below with reference to examples, but the invention of the present disclosure is not limited to these examples.

[0048] <Examples 1 to 7> As the positive electrode active material, LiNi 0.8 (CoAl) 0.2O2 was prepared. The positive electrode active material was surface-treated with LTAF (Li-Ti-Al-F). The positive electrode active material, conductive carbon, solid electrolyte (Li2S-P2S5-LiBr-LiI glass ceramics), binder (styrene butadiene rubber (SBR)), solvent (tetrahydronaphthalene), and copper were mixed using an ultrasonic homogenizer (UH-50 manufactured by SMT Corporation) to obtain a positive electrode mixture paste. The content ratio (volume ratio) of the positive electrode active material and copper was the amount shown in Table 1, and the remaining amounts of conductive carbon, solid electrolyte, and binder were appropriately adjusted to the total amount shown in (Others) in Table 1. The solvent was mixed in an amount of 25 parts by mass when the sum of the contents of the positive electrode active material, conductive carbon, solid electrolyte, binder, and copper was taken as 100 parts by mass.

[0049] Li4Ti5O as negative electrode active material 12 We have prepared the following. The negative electrode active material, conductive carbon, solid electrolyte, binder, and solvent were mixed using an ultrasonic homogenizer (UH-50 manufactured by SMT Co., Ltd.) to obtain a negative electrode mixture paste. The solid electrolyte, binder, and solvent were the same as those used in the positive electrode mixture paste. The content ratio (volume ratio) of the negative electrode active material was the amount shown in Table 1, and the remaining amounts of conductive carbon, solid electrolyte, and binder were appropriately adjusted to the total amount shown in (Others) in Table 1. The solvent was mixed in an amount of 35 parts by mass when the sum of the contents of the negative electrode active material, conductive carbon, solid electrolyte, and binder was taken as 100 parts by mass.

[0050] A polypropylene container was charged with 3 parts by mass of a solution containing 51 parts by mass of a solvent and 5 parts by mass of a binder, and 46 parts by mass of LiI-LiBr-Li2S-P2S5-based glass ceramic as a solid electrolyte, and mixed for 30 seconds using an ultrasonic homogenizer (UH-50 manufactured by SMT). The same binder and solvent as those used in the positive electrode mixture paste were used. Next, the container was shaken with a shaker for 3 minutes to obtain a solid electrolyte paste.

[0051] The positive electrode mixture paste was applied onto an aluminum foil by a blade method using an applicator, and then dried for 30 minutes on a hot press at 100° C. to obtain a positive electrode sheet having a positive electrode layer on the surface of the aluminum foil. In the same manner, the negative electrode mixture paste was applied onto an aluminum foil and dried to obtain a negative electrode sheet having a negative electrode layer. Similarly, the solid electrolyte paste was applied onto an aluminum foil and dried to obtain a solid electrolyte sheet having a solid electrolyte layer. The negative electrode area weight was adjusted so that the negative electrode capacity was 1-fold the specific charge capacity of the positive electrode layer when the specific charge capacity was 200 mAh / g.

[0052] The negative electrode sheet and the solid electrolyte sheet were laminated and pressed to transfer the solid electrolyte layer onto the surface of the negative electrode layer of the negative electrode sheet. Next, a positive electrode sheet was laminated on the side of the solid electrolyte layer opposite to the negative electrode layer side, and roll pressed at 175° C. and 5 ton / cm to obtain a laminate. The laminate had an aluminum foil, a positive electrode layer, a solid electrolyte layer, a negative electrode layer, and an aluminum foil in this order. The obtained laminate was sealed and restrained at 5 MPa to obtain an all-solid-state lithium-ion secondary battery. The all-solid-state lithium-ion secondary battery was left in an environment at 80°C for 7 days.

[0053] <Examples 8 to 16> The positive electrode active material, conductive carbon, solid electrolyte, binder, and solvent were mixed using an ultrasonic homogenizer (UH-50 manufactured by SMT Co., Ltd.) to obtain a positive electrode mixture paste. The various materials used were the same as those used in Example 1. The content ratio (volume ratio) of the positive electrode active material was the amount shown in Table 1, and the remaining amounts of conductive carbon, solid electrolyte, and binder were appropriately adjusted to the total amount shown in (Others) in Table 1. The solvent was mixed in an amount of 25 parts by mass when the sum of the contents of the positive electrode active material, conductive carbon, solid electrolyte, and binder was taken as 100 parts by mass.

[0054] The negative electrode active material, conductive carbon, solid electrolyte, binder, solvent, and copper were mixed using an ultrasonic homogenizer (UH-50 manufactured by SMT Co., Ltd.) to obtain a negative electrode mixture paste. The various materials used were the same as those used in Example 1. The content ratio (volume ratio) of the negative electrode active material and copper was the amount shown in Table 1, and the remaining amounts of conductive carbon, solid electrolyte, and binder were appropriately adjusted to the total amount shown in (Others) in Table 1. The solvent was mixed in an amount of 35 parts by mass when the sum of the contents of the negative electrode active material, conductive carbon, solid electrolyte, binder, and copper was taken as 100 parts by mass.

[0055] Except for using the above positive electrode mixture paste and negative electrode mixture paste, an all-solid-state lithium ion secondary battery was obtained in the same manner as in Example 1. Thereafter, the battery was left to stand for 7 days under the same conditions as in Example 1, that is, in an environment at a temperature of 80°C.

[0056] <Comparative Example 1> The positive electrode active material, conductive carbon, solid electrolyte, binder, and solvent were mixed using an ultrasonic homogenizer (UH-50 manufactured by SMT Co., Ltd.) to obtain a positive electrode mixture paste. The various materials used were the same as those used in Example 1. The content ratio (volume ratio) of the positive electrode active material was the amount shown in Table 1, and the remaining amounts of conductive carbon, solid electrolyte, and binder were appropriately adjusted to the total amount shown in (Others) in Table 1. The solvent was mixed in an amount of 25 parts by mass when the sum of the contents of the positive electrode active material, conductive carbon, solid electrolyte, and binder was taken as 100 parts by mass.

[0057] Except for using the above positive electrode mixture paste, an all-solid-state lithium ion secondary battery was obtained in the same manner as in Example 1. Thereafter, the battery was left to stand for 7 days under the same conditions as in Example 1, that is, in an environment at a temperature of 80°C.

[0058] <Comparative Example 2> The negative electrode active material, conductive carbon, solid electrolyte, binder, solvent, and copper were mixed using an ultrasonic homogenizer (UH-50 manufactured by SMT Co., Ltd.) to obtain a negative electrode mixture paste. The various materials used were the same as those used in Example 1. The content ratio (volume ratio) of the negative electrode active material and copper was the amount shown in Table 1, and the remaining amounts of conductive carbon, solid electrolyte, and binder were appropriately adjusted to the total amount shown in (Others) in Table 1. The solvent was mixed in an amount of 35 parts by mass when the sum of the contents of the negative electrode active material, conductive carbon, solid electrolyte, binder, and copper was taken as 100 parts by mass.

[0059] Except for using the above negative electrode mixture paste, an all-solid-state lithium ion secondary battery was obtained in the same manner as in Example 8. Thereafter, the battery was left to stand for 7 days under the same conditions as in Example 1, that is, in an environment at a temperature of 80°C.

[0060] <<Resistance evaluation>> The obtained all-solid-state lithium ion secondary battery was placed in a thermostatic chamber set at 25° C. and connected to a charge / discharge device. The cells were charged at a constant current equivalent to 0.1 C, and then at a constant voltage after the cell voltage reached 2.7 V. The constant voltage charging test was terminated when the current value reached the equivalent of 0.01 C. Next, the battery was discharged at a constant current of 0.1 C up to 2.12 V, which corresponds to SOC40, and then discharged at a constant voltage of 2.12 V. When the current value reached 0.01 C, the constant voltage discharge was terminated. Thereafter, the battery was discharged at a constant current of 72 C, and the DC resistance was calculated from the voltage after 0.1 seconds according to Ohm's law. Table 1 shows the ratio of the resistance values ​​of each Example and Comparative Example when the resistance value of the all-solid-state lithium ion secondary battery of Comparative Example 1 is taken as 100%.

[0061] [Table 1]

[0062] From the results in Table 1, it can be seen that the solid-state battery of the Example, in which the content of metal (copper) relative to the total volume of the electrode for the solid-state battery is 5 ppm by volume or more, has a reduced resistance increase rate compared to the solid-state battery of Comparative Example 1, in which no metal is contained. It can also be seen that the solid-state battery of the Example, in which the content of metal (copper) relative to the total volume of the electrode for the solid-state battery is less than 10,000 ppm by volume, has a reduced resistance increase rate compared to the solid-state battery of Comparative Example 2, in which the content of metal (copper) exceeds this range.

[0063] The details of the test for confirming that copper is a metal that reacts with the sulfide solid electrolyte to exhibit electronic conductivity will be described later.

[0064] <Examples 17 to 20 and Comparative Examples 3 and 4> The negative electrode active material, conductive carbon, solid electrolyte, binder, solvent, and silver were mixed using an ultrasonic homogenizer (UH-50 manufactured by SMT Co., Ltd.) to obtain a negative electrode mixture paste. The various materials used were the same as those used in Example 1. The content ratio (volume ratio) of the negative electrode active material and silver was the amount shown in Table 2, and the remaining amounts of conductive carbon, solid electrolyte, and binder were appropriately adjusted to the total amount shown in (Others) in Table 2. The solvent was mixed in an amount of 35 parts by mass when the sum of the contents of the positive electrode active material, conductive carbon, solid electrolyte, binder, and silver was taken as 100 parts by mass.

[0065] Except for using the above negative electrode mixture paste, an all-solid-state lithium ion secondary battery was obtained in the same manner as in Example 8. Thereafter, the battery was left to stand for 7 days under the same conditions as in Example 1, that is, in an environment at a temperature of 80°C.

[0066] <<Resistance evaluation>> For the obtained all-solid-state lithium ion secondary battery, a resistance evaluation was carried out in the same manner as in Example 1. Table 2 shows the ratio of the resistance values ​​of each Example and Comparative Example when the resistance value of the all-solid-state lithium ion secondary battery of Comparative Example 1 is taken as 100%.

[0067] [Table 2]

[0068] From the results in Table 2, it can be seen that the solid-state batteries of the examples in which the metal (silver) content relative to the total volume of the electrode for the solid-state battery was 5 volume ppm or more and less than 10,000 volume ppm had a reduced resistance increase rate compared to the solid-state batteries of the comparative examples in which the metal (silver) content was 10,000 volume ppm or more.

[0069] The details of the test for confirming that silver is a metal that reacts with the sulfide solid electrolyte to exhibit electronic conductivity will be described later.

[0070] <Comparative Examples 5 to 8> The negative electrode active material, conductive carbon, solid electrolyte, binder, solvent, and stainless steel SUS316 were mixed using an ultrasonic homogenizer (UH-50 manufactured by SMT Co., Ltd.) to obtain a negative electrode mixture paste. The various materials used were the same as those used in Example 1. The content ratio (volume ratio) of the negative electrode active material and the stainless steel SUS316 was the amount shown in Table 3, and the remaining amounts of the conductive carbon, solid electrolyte, and binder were appropriately adjusted to the total amount shown in (Others) in Table 3. The solvent was mixed in an amount of 35 parts by mass when the sum of the contents of the positive electrode active material, conductive carbon, solid electrolyte, binder, and stainless steel SUS316 was taken as 100 parts by mass.

[0071] Except for using the above negative electrode mixture paste, an all-solid-state lithium ion secondary battery was obtained in the same manner as in Example 8. Thereafter, the battery was left to stand for 7 days under the same conditions as in Example 1, that is, in an environment at a temperature of 80°C.

[0072] <<Resistance evaluation>> For the obtained all-solid-state lithium ion secondary battery, a resistance evaluation was carried out in the same manner as in Example 1. Table 3 shows the ratio of the resistance value of each comparative example when the resistance value of the all-solid-state lithium ion secondary battery of Comparative Example 1 is taken as 100%.

[0073] [Table 3]

[0074] From the results in Table 3, it can be seen that the rate of increase in resistance was not reduced in the solid-state battery of the comparative example in which the electrode for the solid-state battery contained stainless steel SUS316.

[0075] Details of the confirmation test to verify that stainless steel SUS316 is not a metal that reacts with sulfide solid electrolytes and exhibits electronic conductivity will be described later.

[0076] <Comparative Examples 9 to 10> The positive electrode active material, conductive carbon, solid electrolyte, binder, solvent, and copper were mixed using an ultrasonic homogenizer (UH-50 manufactured by SMT Co., Ltd.) to obtain a positive electrode mixture paste. The various materials used were the same as those used in Example 1. The content ratio (volume ratio) of the positive electrode active material and copper was the amount shown in Table 4, and the remaining amounts of conductive carbon, solid electrolyte, and binder were appropriately adjusted to the total amount shown in (Others) in Table 4. The solvent was mixed in an amount of 25 parts by mass when the sum of the contents of the positive electrode active material, conductive carbon, solid electrolyte, binder, and copper was taken as 100 parts by mass.

[0077] Except for using the above positive electrode mixture paste, an all-solid-state lithium ion secondary battery was obtained in the same manner as in Example 1. Thereafter, the battery was left to stand for 7 days under the same conditions as in Example 1, that is, in an environment at a temperature of 80°C.

[0078] <Comparative Example 11> The negative electrode active material, conductive carbon, solid electrolyte, binder, solvent, and copper were mixed using an ultrasonic homogenizer (UH-50 manufactured by SMT Co., Ltd.) to obtain a negative electrode mixture paste. The various materials used were the same as those used in Example 1. The content ratio (volume ratio) of the negative electrode active material and copper was the amount shown in Table 4, and the remaining amounts of conductive carbon, solid electrolyte, and binder were appropriately adjusted to the total amount shown in (Others) in Table 4. The solvent was mixed in an amount of 35 parts by mass when the sum of the contents of the negative electrode active material, conductive carbon, solid electrolyte, binder, and copper was taken as 100 parts by mass.

[0079] Except for using the above negative electrode mixture paste, an all-solid-state lithium ion secondary battery was obtained in the same manner as in Example 1. Thereafter, the battery was left to stand for 7 days under the same conditions as in Example 1, that is, in an environment at a temperature of 80°C.

[0080] <<Short circuit suppression evaluation (self-discharge amount evaluation)>> The obtained all-solid-state lithium ion secondary battery was placed in a thermostatic chamber set at 25° C. and connected to a charge / discharge device. Constant voltage charging was performed at 2.515 V. The constant voltage charging was terminated when the current value attenuated to 0.01 C. The battery voltage was then measured at the open circuit voltage for 72 hours. The voltage drop over the 24 hours between 48 and 72 hours was calculated as the self-discharge amount. The self-discharge amount was measured for Examples 3 to 7, Examples 11 to 16, Comparative Examples 1 to 2, and Comparative Examples 9 to 11. The results are shown in Table 4.

[0081] [Table 4]

[0082] From the results in Table 4, it can be seen that the solid-state batteries of Examples 3 to 6 and Examples 11 to 15, in which the metal (copper) content relative to the total volume of the electrode for the solid-state battery was 4000 volume ppm or less, had smaller self-discharge amounts and improved short-circuit suppression properties compared to the solid-state batteries of Examples 7 and 16, in which the metal (copper) content exceeded 4000 volume ppm, and the comparative solid-state batteries.

[0083] <Examples 21 to 25> The positive electrode active material, conductive carbon, solid electrolyte, binder, solvent, and copper were mixed using an ultrasonic homogenizer (UH-50 manufactured by SMT Co., Ltd.) to obtain a positive electrode mixture paste. The various materials used were the same as those used in Example 1. The content ratio (volume ratio) of the positive electrode active material and copper was the amount shown in Table 5, and the remaining amounts of conductive carbon, solid electrolyte, and binder were appropriately adjusted to the total amount shown in (Others) in Table 5. The solvent was mixed in an amount of 25 parts by mass when the sum of the contents of the positive electrode active material, conductive carbon, solid electrolyte, binder, and copper was taken as 100 parts by mass.

[0084] The negative electrode active material, conductive carbon, solid electrolyte, binder, solvent, and copper were mixed using an ultrasonic homogenizer (UH-50 manufactured by SMT Co., Ltd.) to obtain a negative electrode mixture paste. The various materials used were the same as those used in Example 1. The content ratio (volume ratio) of the negative electrode active material and copper was set to the amounts shown in Table 5, and the remaining amounts of conductive carbon, solid electrolyte, and binder were appropriately adjusted to the total amounts shown in (Others) in Table 5. The solvent was mixed in an amount of 35 parts by mass when the sum of the contents of the negative electrode active material, conductive carbon, solid electrolyte, binder, and copper was taken as 100 parts by mass.

[0085] Except for using the above positive electrode mixture paste and negative electrode mixture paste, an all-solid-state lithium ion secondary battery was obtained in the same manner as in Example 1. Thereafter, the battery was left to stand for 7 days under the same conditions as in Example 1, that is, in an environment at a temperature of 80°C.

[0086] <<Resistance evaluation>> For the obtained all-solid-state lithium ion secondary battery, a resistance evaluation was carried out in the same manner as in Example 1. Table 5 shows the ratio of the resistance value of each comparative example when the resistance value of the all-solid-state lithium ion secondary battery of Comparative Example 1 is taken as 100%.

[0087] <<Short circuit suppression evaluation (self-discharge amount evaluation)>> The short circuit suppression ability of the obtained all-solid-state lithium ion secondary battery was evaluated in the same manner as in Example 1. The results of the self-discharge amount are shown in Table 5.

[0088] [Table 5]

[0089] <<Verification of whether a metal is a specific metal>> The above-mentioned verification method was used to check whether the copper, silver, and stainless steel SUS316 used in the above examples, as well as nickel, aluminum, gold, iron, platinum, and zinc, which were not used in the above examples, are metals (specific metals) that react with sulfide solid electrolytes to exhibit electronic conductivity. The measured increase rate of electronic conductivity before and after heat treatment is shown in Table 6.

[0090] [Table 6] [Explanation of symbols]

[0091] A: negative electrode layer, B: solid electrolyte layer, C: positive electrode layer, 101: negative electrode active material, 103: positive electrode active material, 105 and 107: conductive assistant, 109 and 111: binder, 113: negative electrode current collector, 115: positive electrode current collector

Claims

1. A sulfide solid electrolyte; A metal that reacts with the sulfide solid electrolyte to exhibit electronic conductivity; Contains A solid-state battery electrode, wherein the content of the metal relative to the total volume of the electrode is 5 ppm by volume or more and less than 10,000 ppm by volume.

2. 2. The electrode for a solid state battery according to claim 1, wherein the metal is at least one metal selected from the group consisting of copper, silver, nickel, iron, tin, aluminum, titanium, chromium, zinc, gold, magnesium, antimony, zirconium, molybdenum, and alloys thereof.

3. The electrode for a solid-state battery according to claim 2 , wherein the metal is at least one of copper and silver.

4. 2. The electrode for a solid state battery according to claim 1, wherein a content of the metal relative to a total volume of the electrode for a solid state battery is 50 ppm by volume or more.

5. 2. The electrode for a solid state battery according to claim 1, wherein a content of the metal relative to a total volume of the electrode for a solid state battery is 5,000 ppm by volume or less.

6. The electrode for a solid-state battery according to claim 1 , wherein the sulfide solid electrolyte contains phosphorus atoms.

7. A solid-state battery comprising a positive electrode layer, a solid electrolyte layer, and a negative electrode layer, A solid-state battery, wherein at least one of the positive electrode layer and the negative electrode layer is the electrode for a solid-state battery according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • All solid lithium battery

    JP1996138725A

  • Electrode for all-solid battery, and all-solid battery

    JP2012133932A

  • Electrode of power storage device using solid electrolyte, power storage device, and method of manufacturing positive electrode layer or negative electrode layer of power storage device

    JP2020136099A

  • Method of manufacturing sulfide all-solid-state battery

    JP2020191183A